PEMANFAATAN SINYAL PUTARAN GENERATOR DARI DCS UNTUK PENGGANTIAN SPEED RELAY ELEKTRO MEKANIK PADA SISTEM EKSITASI GENERATOR HIDRO - Mustaqimul Hadi; Fikri Wahyudi; Herris Yamashika (Rang Teknik Journal, 2026)
The Maninjau Hydroelectric Power Plant (HEPP) faces technical challenges in its generator excitation system due to failures in the Type 13 electromechanical speed relay, a critical component in the excitation start-up sequence. This relay has not only lost accuracy but is also obsolete and difficult to procure in the market. Its malfunction poses the risk of excitation sequence failure, which may lead to damage in the Automatic Voltage Regulator (AVR), voltage meter disturbances, and even complete unit start-up failure.This study aims to replace the function of the electromechanical speed relay with a system utilizing generator rotational speed signals available through the Distributed Control System (DCS). The Root Cause Problem Solving (RCPS) method, field observation, and priority matrix analysis were employed to evaluate the most optimal replacement alternative. The results indicate that using a 24VDC relay based on signals from the Speed Sensor Gear (SSG) and digital signals from the DCS provides the best solution. The new system enables a more precise excitation process, easier installation, improved safety, as well as real-time monitoring and full integration with digital control systems.The implemented modification demonstrates that the excitation system becomes more reliable and efficient, effectively overcoming the previously frequent excitation sequence failures. Furthermore, the system is considered more economical and universal, while ensuring compatibility with future developments in digital-based power plant technology. Overall, this research makes a significant contribution to the modernization of hydroelectric control systems, in line with the sustainable and technology-driven development of national power infrastructure.Keywords: Speed Relay, DCS, Excitation System, Hydroelectric Power Plant, Generator Rotational Speed, Control Modernization